1999
DOI: 10.4141/p98-108
|View full text |Cite
|
Sign up to set email alerts
|

Control of postharvest gray mold rot of modified atmosphere packaged sweet cherries by fumigation with thymol and acetic acid

Abstract: R. 1999. Control of postharvest gray mold rot of modified atmosphere packaged sweet cherries by fumigation with thymol and acetic acid. Can. J. Plant Sci. 79: 685-689. Hedelfingen sweet cherries (Prunus avium L.) were inoculated with spores of Botrytis cinerea and then fumigated with 30 mg L -1 of thymol, acetic acid, or ethanol for 25 min before sealing in modified atmosphere packages and placing into cold storage. After 10 wk of storage, thymol or acetic acid reduced gray mold rot of B. cinerea inoculated ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 14 publications
1
27
0
3
Order By: Relevance
“…Previously, it was shown that vaporized thymol could control postharvest decay for the cherries inoculated with Botrytis cinerea [17], but our study is the first time it has been presented that thymol inhibited the disease-causing pathogens on cherries inoculated with M. fructicola. Our study also showed that thymol caused more severe phytotoxicity than acetic acid.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Previously, it was shown that vaporized thymol could control postharvest decay for the cherries inoculated with Botrytis cinerea [17], but our study is the first time it has been presented that thymol inhibited the disease-causing pathogens on cherries inoculated with M. fructicola. Our study also showed that thymol caused more severe phytotoxicity than acetic acid.…”
Section: Discussionmentioning
confidence: 80%
“…Our previous study revealed that fumigation with thymol was more effective than acetic acid to prevent gray mold rot [17]. However, at 30 mg × L -1 , thymol-treated cherries showed more stem browning than those treated with acetic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Eugenol från kryddnejlikor och basilika är den mest aktiva komponenten mot svampangrepp (B. cinerea och M. fructigena) hos äpple (Amiri et el., 2008). Växtoljor och flyktiga ämnen, från pepparmynta, lavendel och sojabönor har också visat sig ha en hämmande effekt på B. cinerea (Chu et al, 1999), M. fructicola, i körsbär (Chu et al, 2001) och i aprikos (Liu and Chu, 2002 …”
Section: Bioaktiva Föreningarunclassified
“…On the other hand, acetic acid (AA) in air at low concentrations is not flammable, explosive, or carcinogenic [12] and is very effective against molds such as P. expansum that cause storage decay [13]. Subsequent studies showed that AA fumigation would control postharvest decay caused by other pathogens such as Monilinia fructicola and Botrytis cinerea on apricots [14], cherries [15,16], citrus [16], grapes [17], peaches [14], nectarines [14] and strawberries [18]. Acetic acid vapor treatment for the control of postharvest decay has been reviewed [19] identifying additional uses in food processing and modified atmosphere packaging.…”
Section: Introductionmentioning
confidence: 99%